Complementary roles of platelet αIIbβ3 integrin, phosphatidylserine exposure and cytoskeletal rearrangement in the release of extracellular vesicles. (October 2020) - Heinzmann, Alexandra C.A.; Karel, Mieke F.A.; Coenen, Daniëlle M.; Vajen, Tanja; Meulendijks, Nicole M.M.; Nagy, Magdolna; Suylen, Dennis P.L.; Cosemans, Judith M.E.M.; Heemskerk, Johan W.M.; Hackeng, Tilman M.; Koenen, Rory R.
Abstract: Background and aims: Platelets can release extracellular vesicles (EVs) upon stimulation with various agonists. Interestingly, platelets from patients with Glanzmann thrombasthenia have reduced EV release. These platelets lack functional αIIb β3 integrins, indicating that αIIb β3 integrin is critical in vesicle release. Integrin activation is central in platelet function and is associated with e.g. adhesion, aggregation and cytoskeletal rearrangement. However, while platelet activation pathways are widely known, the mechanisms underlying EV release remain uncharacterized. We investigated the role of integrin αIIb β3, phosphatidyl serine (PS) exposure, cytoskeletal rearrangement and their associated signalling pathways in EV release. Methods: EVs were isolated from activated platelets. Platelet activation status was measured by multicolour flow cytometry. A panel of pharmacologic inhibitors was used to interfere in specific signalling pathways. EV release was quantified enzymatically based on membrane PS content and nanoparticle tracking analysis. In addition, real-time visualization of EV shedding with confocal microscopy and EVs with Cryo-TEM imaging was performed. Results: Platelet activation with convulxin resulted in higher EV release than with activation by thrombin. Kinetic measurements indicated that EV release followed the pattern of αIIb β3 integrin activation and subsequent closure paralleled by PS exposure. Prevention of αIIb β3 activation with the inhibitor tirofiban dramatically suppressed EV release. Similar results were obtained using αIIb β3 -deficient platelets from patients with Glanzmann thrombasthenia. Inhibition of actin cytoskeleton rearrangement decreased EV release, whereas inhibition of individual signalling targets upstream of cytoskeletal rearrangement showed no such effects. Conclusion: Platelet EV release requires three main events: integrin activation and closure, PS exposure, and cytoskeletal rearrangement. Graphical abstract: Image 1 Highlights: Inhibition or genetic deficiency of integrin αIIb β3 results in a strong decrease of vesicle formation by activated platelets. Cytoskeletal rearrangement is required for vesicle release after platelet activation. Vesicle release requires integrin activation and closure, negative phospholipid exposure and cytoskeletal rearrangement.